Pathways to youth empowerment and community connectedness: a study of youth-adult partnership in Malaysian after-school, co-curricular programs - Zeldin, Shepherd; Krauss, Steven Eric; Kim, Taehan; Collura, Jessica; Abdullah, Haslinda (Springer Verlag, 2016)
After-school programs are prevalent across the world, but there is a paucity of research that examines quality within the “black box” of programs at the point of service. Grounded in current theory, this research examined hypothesized pathways between the experience of youth-adult partnership (youth voice in decision-making; supportive adult relationships), the mediators of program safety and engagement, and the developmental outcomes of youth empowerment (leadership competence, policy control) and community connectedness (community connections, school attachment). Surveys were administered to 207 ethnically diverse (47.3 % female; 63.3 % Malay) youth, age 15–16, attending after-school co-curricular programs in Kuala Lumpur, Malaysia. Results showed that youth voice in program decision-making predicted both indicators of youth empowerment. Neither youth voice nor supportive adult relationships was directly associated with community connectedness, however. Program engagement mediated the associations between youth-adult partnership and empowerment. In contrast, program safety mediated the associations between youth-adult partnership and community connectedness. The findings indicate that the two core components of youth-adult partnership—youth voice and supportive adult relationships—may operate through different, yet complementary, pathways of program quality to predict developmental outcomes. Implications for future research are highlighted. For reasons of youth development and youth rights, the immediate challenge is to create opportunities for youth to speak on issues of program concern and to elevate those adults who are able and willing to help youth exercise their voice.